Another look at risk-based capital regime, capital structure, insurer's risk profile and performance: a conceptual paper - Akpan, Sunday Sunday; Mahat, Fauziah; Amin Noordin, Bany Ariffin; Md Nassir, Annuar (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper evaluates capital structure under risk-based capital regime from the perspective of insurance firms and its performance. It also evaluates the moderating effect of insurer’s risk profile on capital-performance relationship. The authors aim to reveal ambiguities, gaps and omissions in the literature and to sketch avenues for future research. A conceptual framework for capital structure under risk-based capital era and its application is suggested focusing on equity, technical provision and required risk propensity for maximizing profit and wealth for all stakeholders. The research reviews that capital structure of insurers differs from non-insurance firms as such risk-based capital regulation must not only focus on the various types of risk but also recognized these differences. It is shown that insurers’ capital structure contains equity and technical provisions which comprises creditors and accruals, outstanding claims and insurance funds instead of equity and financial debt as it is with conventional non insurance firms. This study thus stressed that for capital structure to best explain performance of insurers, it must be measured by equity ratio and technical provision ratio in place of debt ratio and corporate risk profile (quantitative and qualitative) must enter its sequence of performance relational analysis and effectiveness equations. We stressed further that only with the proposed conceptual framework would a holistic understanding of insurer’s capital structure be achieved while the observed contradictory and inconclusive empirical findings on capital structure and firm performance could be resolved.